Overweight and obesity profiles in Niger Delta Region, Nigeria - Alphhonsus U. Idung; Festus Abasiubong; Sunday B. Udoh; Uwemedimbuk S. Ekanem (AOSIS, 2014)
Introduction: Overweight and obesity are global public health problems because of their effect on individuals, families and communities. The objective of this study was to describe the profile of overweight and obesity amongst adult out patients in Uyo in the Niger Delta region of Nigeria. Method: This was a cross-sectional descriptive study done between October 2011 and March 2012. Using a systematic sampling technique, 584 subjects aged 18-65 years were recruited; data were collected with a structured questionnaire. Subjects were measured for height, weight, waist and hip circumferences. Body mass index (BMI) and waist-hip ratio (WHR) were calculated. Subjects with a BMI of 25.0 kg/m2 - 29.9 kg/m2 were regarded as being overweight whilst a BMI of > 30.0 kg/m2 was regarded as obese. Subjects with a WHR of > 0.90 for men or > 0.85 for women were regarded as having abnormal WHR. Results: Of the 584 subjects, 196 (36.6%) were men and 388 (66.4%) women. The mean age for men and women was 43.3 ± 17.8 years and 50.2 ± 13.6 years, respectively. The prevalence of overweight amongst men was 39.8% versus 31.7% for women; obesity in men was 28.0% versus 52.0% in women. Overweight and obesity were more prevalent in subjects aged 25-54 years and amongst married subjects. There was a significant relationship between obesity and television viewing (p = 0.003). Hypertension (p = 0.008) and osteoarthropathies (p = 0.043) were more prevalent amongst the obese than the non-obese subjects. Conclusion: Overweight and obesity are now common in our environment. There is therefore a need for more public education about the health consequences of big body size.